Descriptive Analysis of Interpretive Ability of Supporting Examinations in Emergency Cases of Medical Professional Study Program Students - Fitria, Luthfi Irma; Romadhoni, Romadhoni; Novitasari, Andra; Arfiyanti, Mega Pandu; Hajar, Nabil (Universitas Padjadjaran, 2025)
Medical competence is an important index to prepare students to enter the clinical stage in the education process. One of the competencies of doctors in Indonesia is 3B, which is the ability to deal with emergency cases. Patients who experience emergencies must receive immediate help and proper treatment. If the treatment is not appropriate, it can result in patient disability and even death. The purpose of the study was to analyze the ability of doctor study program to interpret supporting examinations in the form of ECG in emergency cases. This study is a quantitative study with a descriptive analytic method with cross sectional design. The samples of this study were all UNIMUS medical professional program students who participated in the UKMPPD OSCE tryout in May 2023 period which was taken through the total sampling technique. This study uses secondary data consisting of the results of ECG interpretation scores and the final results of the stase assessment given by the examining lecturer. The results of the study with 41 samples showed that the majority of students answered incorrectly on heart rate frequency (53.7%), P wave (65.9%) and PR interval (75.6%). While the majority of students answered correctly on rhythm (56.1%), axis (58.5%), transition zone (63.4%), QRS complex (58.5%), ST segment (51.2%) and conclusion (61%). Based on the Competency Test for Medical Professional Program Students OSCE try-out score, most of the sample did not pass (65.9%). The ability of medical professional study program students to interpret supporting examinations in the form of ECG in emergency cases in cardiovascular staging is categorized as low. Keywords: EKG; emergency; OSCE; try out